Manuel Viñals de la Torre y el archivo de la inquisición de Barcelona (1705-1723) - Santiago Medina, Bárbara (Revista General de Información y Documentación, 2006)
When the Archiduke Carlos de Austria’s troops were near the city of Barcelona, during the Spanish Sucession War, the inquisitors and other ministries of the catalonian Inquisition escaped to Tortosa, a safer place. Before travelling to this city, they left the Holly Office of Barcelona’s management to Manuel Viñals de la Torre, the “Secretario del Secreto” (a secretary that was in charge of the inquisitorial archive). After this, during Barcelona’s siege, Viñals became the most important defender of “his” Inquisition from the political and Church’s attacks that were sent versus the institution in order to diminish its power. This investigation tries to explain the history of this archive during this period of decay; a period almost unknown and forgotten by the Inquisition’s contemporary historians.